1422. Real-World Study of the Effects of Inappropriate or Suboptimal Treatment on the Burden of Illness Among Patients with Uncomplicated Urinary Tract Infection and High-Risk Comorbid Conditions in the United States. (4th December 2021) - Preib, Madison T; Marijam, Alen; Mitrani-Gold, Fanny S; Gibbons, Daniel C; Sun, Xiaoxi; Adams, Christopher; Joshi, Ashish V
Abstract: Background: Urinary tract infections (UTIs) are associated with significant morbidity and economic burden. Nitrofurantoin (NFT) and fosfomycin are among the first-line treatments for uncomplicated UTI (uUTI) recommended by Infectious Diseases Society of America (IDSA) 2011 guidance. We used real-world data (RWD) to assess patterns of appropriate and optimal (AP&OP) and inappropriate or suboptimal (IA/SO) antibiotic (AB) prescribing (RX), and related healthcare resource use (HRU) and costs, in US uUTI patients with high-risk comorbid conditions. Methods: This was a retrospective cohort study of RWD (IBM MarketScan, commercial/Medicare Supplemental claims January 1, 2014–December 31, 2017) in females ≥ 12 years of age with uUTI, who had an oral AB prescription ± 5 days of uUTI diagnosis (index date) and continuous health-plan enrollment ≥ 1 year pre-/post-index date. Patients were stratified into high-risk cohorts (Table 1 ) and by AB RX (AP&OP and IA/SO) during first uUTI episode (within 28 days of index). AP&OP RX followed IDSA guidance, IA RX did not; SO RX was considered a proxy for treatment failure (e.g., AB switch or a second UTI diagnosis [acute care setting] in index episode). Sample size was balanced via random match selection, AP&OP:IA/SO ratio 1:5 (age and region). uUTIrelated HRU and costs were compared between cohorts (at index episode and 1-year follow-up) via multivariable analysis. Table 1. High-risk cohorts identified in the study Results: IA/SO AB RX was highest in the elderly cohort (94.3%, likely influenced by renal impairment/no NFT RX in this group) and > 90% in other cohorts; AP&OP AB RX was highest in the postmenopausal cohort (9.0%). IA/SO AB RX in all cohorts was associated with significantly higher uUTI-related HRU (outpatient visits and pharmacy claims) per index episode/during follow-up versus AP&OP AB RX (p ≤ 0.0237, Table 2 ). IA/SO AB RX in all cohorts was associated with significantly higher adjusted total costs per index episode/during follow-up versus AP&OP AB RX (p < 0.05; Table 3 ). Table 2. uUTI-related HRU* per patient according to high-risk cohort and stratified by AB RX Table 3. uUTI-related costs* per patient according to high-risk cohort and stratified by AB RX Conclusion: Over 90% of females in each high-risk cohort identified had IA/SO AB RX (outside IDSA 2011 guidance for uUTI treatment), leading to high HRU and cost burden. This suggests an unmet need for uUTI symptom relief, new treatments, training, and improved RX practices in the US and, furthermore, a need for additional research in this area. Disclosures: Madison T. Preib, MPH, STATinMED Research (Employee, Former employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Alen Marijam, MSc, GlaxoSmithKline plc. (Employee, Shareholder) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder) Daniel C. Gibbons, PhD, GlaxoSmithKline plc. (Employee, Shareholder) Xiaoxi Sun, MA, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Christopher Adams, MPH, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder)